Sperm quality and testicular histopathology of Wistar albino male rats treated with hydroethanolic extract of Cordia dichotoma fruits - Samah A. El-Newary; Mohamed S. Aly; Amal R. Abd El Hameed; Mohamed S. Kotp; Abdelghany A. Youssef; Naglaa A. Ali (Taylor & Francis Group, 2022)
Context Cordia dichotoma Forst. (Boraginaceae) has potent pharmacological impact. Meanwhile, its effect on fertility is unclear. Objective This study investigates the effect of Cordia fresh fruits hydroethanolic extract on fertility. Materials and methods 120 Wistar albino male rats were divided into four groups (n = 30). The first group was negative control, and the second, third, and fourth groups received 125, 250, and 500 mg extract/kg bodyweight for 56 days. After 56 days, Cordia force-feeding stopped, and all groups were kept under laboratory conditions for another month to study the recovering effect. Results After day 56, extract at 500 mg/kg significantly reduced sperm total count, motility%, and alive%, to 47.60 ± 2.27 × 106 sperm/mL, 43.33% ± 1.49, and 63.67% ± 1.19, respectively, abnormalities% increased considerably (26.67% ± 0.54), compared to the negative control. Also, significant depletion on follicle-stimulating hormone (2.66 ± 0.21 mIU/L), luteinizing hormone (1.07 ± 0.06 mIU/L), and testosterone (2.69 ± 0.13 nmol/L) level was recorded, compared to the negative control. Cordia negative effect showed on histopathological studies of testes, prostate, and seminal vesicles. Fortunately, these adverse effects of Cordia recovered remarkably after stopping administration for one month. Conclusions Cordia antifertility effect may be due to its hypocholesterolemic effect, where cholesterol, the steroid cycle precursor, was significantly reduced. This study can be incorporated in clinical research after being repeated on another small experimental animal, their offspring, and one large experimental animal, then going to a clinical study that we plan to do in the future.